Meconium dependence of bowel damage in gastroschisis - Correia-Pinto, J (2002)
Background/Purpose: Increasing evidence of physiologic in utero defecation supports the hypothesis that bowel damage in gastroschisis may be meconium dependent. In this study, the author investigated the role of meconium on parameters of bowel damage in a fetal rat model of gastroschisis. Methods: Pregnant rats underwent laparotomy at 18 1/2 days gestational age (GA). There were 4 experimental groups of 11 fetuses each; the G(M) group consisted of fetuses with isolated gastroschisis and was considered to have moderate meconium contamination of the amniotic fluid (MCAF); the GL group consisted of fetuses with gastroschisis and anal ligation, performed to prevent MCAF; the G(H) group consisted of fetuses with gastroschisis and colon perforation, performed to increase MCAF; and the Sham group consisted of sham operated controls. All fetuses were harvested by cesarean section at 21 1/2 days GA, and the fetal intestine was assessed for peel, intestinal length, intestinal weight per unit length, and histologic appearance. Results. The authors achieved the following fetal survival rates: Gm group, 91% (10 of 11); GL group, 78% (7 of 9, the ligation was not successful in 2 fetuses); G(H) group, 82% (9 of 11). Sham group, 100% (11 of 11). Intestinal length was decreased in fetuses with gastroschisis, and this reduction was related directly to the grade of MCAF (Sham, 18.4 +/- 0.6; G(L), 11.5 +/- 0.5; G(M), 10.2 +/- 0.6; G(H), 9.1 +/- 0.6 cm; P <.01). In contrast, intestinal weight per unit length increased in fetuses with gastroschisis, and this Increase was related directly to the grade of MCAF (Sham, 7.8 +/- 0.5; G(L), 9.4 +/- 0.5; G(M), 11.3 +/- 0.5; G(H), 16.9 +/- 0.7 mg/cm; P<.01). In comparison with the G(M) group, the degree of peel coverage and bowel adherence were increased markedly in the GH group, whereas the fetuses of the GL group had neither peel nor bowel adherence. Conclusions: All bowel damage parameters were affected by MCAF supporting the hypothesis that bowel damage in gastroschisis is at least partially dependent on meconium exposure. Further research is required to clarify other factors that contribute to bowel damage and to identify risk factors that may allow prenatal identification of severely affected fetuses. J Pediatr Surg 37:31-35. Copyright (C) 2002 by W.B. Saunders Company.